Lithium ion extraction method
By using aluminum hydroxide to generate aluminum lithium LDH and performing low-temperature calcination and desorption agent treatment, the problems of low adsorption capacity and difficulty in desorption in the prior art are solved, and efficient extraction and efficient utilization of lithium ions are achieved.
Patent Information
- Application Number
- CN202411379423.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing aluminum lithium LDH adsorbent has a low adsorption capacity of lithium ions, and it is difficult to completely desorb lithium ions after adsorption, resulting in low lithium ions extraction efficiency.
Aluminum hydroxide is used as the adsorption body to generate aluminum lithium LDH through co-precipitation reaction, and after low-temperature roasting, desorption agents (such as magnesium chloride, ferric chloride, magnesium sulfate or ferric sulfate) are used to efficiently desorption of lithium ions to achieve lithium ions efficient extraction.
It significantly improves the adsorption amount and desorption rate of lithium ions, ensures efficient extraction of lithium ions and reversible material recycling, and is suitable for the efficient utilization of low-concentration lithium solutions.
Smart Images

Figure CN119265428A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion enrichment and recovery, and more specifically, to a method for extracting lithium ions. Background Art
[0002] As the demand for batteries continues to rise, lithium has become a key metal that is related to the lifeline of the national economy. Lithium resources include brine, lithium ore (lepidolite, spodumene, etc.), waste lithium-ion batteries, etc. Various forms of lithium resources will be enriched in the solution. The cations in the lithium-containing solution mainly include Li + 、Na + , K + Mg 2+ , Ca 2+ 、Co 2+ 、Ni 2+ , the anion is mainly Cl - 、SO 4 2- , CO 3 2- , HCO 3 - 、NO 3 - OH - . Li in solution + Separation and enrichment methods mainly include precipitation, ion exchange, solvent extraction, membrane separation, electro-deintercalation and adsorption. + The materials involved in separation and enrichment can be divided into organic materials and inorganic materials. Specifically, organic materials include extractants, co-extractants and resins, while inorganic materials mainly include manganese materials, titanium materials, phosphoric acid materials and aluminum materials.
[0003] Among lithium-ion-enriched materials, aluminum-based materials have the strongest selectivity, among which lithium aluminum layered double hydroxides (Li / Al-LDHs) are the most widely used. Li / Al-LDHs have the advantages of simple preparation process, mild synthesis conditions, high lithium selectivity, and low cost. However, the main material, aluminum lithium LDH, has a relatively small adsorption capacity for lithium ions, and it is difficult to completely desorb lithium ions after adsorption.
[0004] For example, the invention patent with application number 202311297293.X discloses a lithium ion adsorbent, a preparation method thereof and a method for extracting lithium ions. The application generates titanium oxide complex anions by adding titanium tetrachloride for hydrolysis, and uses it as the nucleus for the coprecipitation reaction between lithium ions and aluminum ions or aluminate ions, thereby synthesizing titanium oxide doped aluminum lithium LDH, that is, synthesizing lithium aluminum layered double hydroxide (Li / Al-LDHs) by coprecipitation, and using it as an adsorbent to improve the adsorption of lithium ions in lithium-containing solutions by synthesizing Li / Al-LDHs with a larger specific surface area. As the doping ratio of titanium in the adsorbent increases to 50%, the maximum adsorption capacity of the obtained adsorbent reaches 9.9 mg / g, and it is further disclosed that when its doping ratio is higher than 0.5, the adsorption effect of the obtained adsorbent no longer continues to increase.
[0005] For example, the invention patent with application number 201910293887.0 synthesizes lithium aluminum layered double hydroxide (Li / Al-LDHs) by coprecipitation method to extract lithium ions from lithium extraction mother liquor of salt lake brine. The application includes the following steps: S1, adding aluminum salt solution and sodium hydroxide solution to the lithium extraction mother liquor of salt lake brine at the same time, making the three coprecipitate at 25℃~70℃, and keeping the pH of the system at 8~13, to obtain a nucleation system with lithium aluminum hydrotalcite crystal nuclei; S2, heating the nucleation system at 50℃~150℃ After aging for 6h to 48h, solid-liquid separation is performed to obtain a lithium aluminum hydrotalcite filter cake; S3, the lithium aluminum hydrotalcite filter cake is washed and dried to obtain lithium aluminum hydrotalcite; S4, the lithium aluminum hydrotalcite is calcined at 200°C to 800°C for 10min to 100min, the calcined product is soaked in water, and after solid-liquid separation, a lithium-containing solution is obtained; S5, the lithium-containing solution is concentrated and enriched in an electrodialysis system to obtain a concentrated lithium-rich solution; S6, the concentrated lithium-rich solution is evaporated, concentrated and crystallized in an MVR system under vacuum or inert gas protection to obtain lithium hydroxide. In step S4, it is preferred to use a multi-stage circulating leaching method to soak the calcined product; this application desorbs the lithium aluminum hydrotalcite by soaking in water to precipitate Li + Ions, under this desorption mode, aluminum-lithium LDH cannot completely desorb lithium ions. Summary of the invention
[0006] In view of the relatively low adsorption capacity of existing aluminum-lithium LDH adsorbents for lithium ions and the technical problems that lithium ions cannot be completely desorbed after adsorption, the present scheme provides a method for extracting lithium ions. The present invention uses aluminum hydroxide as the adsorption body to adsorb lithium ions and generate aluminum-lithium LDH, thereby effectively increasing the adsorption capacity of aluminum hydroxide for lithium ions. At the same time, low-temperature calcination and desorbents are used to efficiently desorb lithium ions in the generated aluminum-lithium LDH, greatly improving the extraction effect of lithium ions.
[0007] The invention provides a method for extracting lithium ions, comprising: contacting or mixing active aluminum hydroxide with an alkaline lithium-containing solution to generate aluminum-lithium LDH, and realizing the adsorption of lithium ions in the lithium-containing solution; low-temperature roasting the generated aluminum-lithium LDH, wherein the roasting temperature is 200-600°C; desorbing the roasted product by a desorbent, and obtaining a lithium-rich solution and a desorbed slag after solid-liquid separation, wherein the desorbent is magnesium chloride, ferric chloride, magnesium sulfate or ferric sulfate solution; and alkali dissolving the desorbed slag to form an aluminum salt solution and an alkaline-dissolved slag, wherein the aluminum salt solution is used to prepare active aluminum hydroxide and is recycled.
[0008] AlLi-LDH is a special layered material in which the formation of Al-O octahedral rings has an important influence on its ability to adsorb lithium ions. After the adsorption of lithium ions, the space group of this material changes from the original P32 or C2 / m to P32. This change in space group makes it easier for AlLi-LDH to adsorb lithium ions. However, this adsorption process is not just physical adsorption, but also involves the role of chemical adsorption, which makes the interaction between the Al-O octahedral ring and lithium ions stronger. Specifically, when AlLi-LDH adsorbs lithium ions, the Li-O interaction belongs to the electrostatic effect, and the strength of this interaction becomes weaker at the P32 space group, but even so, due to the strong rigidity of the Al-O octahedral ring, the selectivity for lithium ions is also the strongest, which increases the adsorption capacity of aluminum-lithium layered double hydroxide for lithium ions to a certain extent, but also makes it difficult to desorb these ions by simple physical methods. In addition, the adsorption process of AlLi-LDH also involves complex chemical and physical processes, including ion exchange and electrostatic attraction, which make the aluminum-lithium layered double hydroxide have high selectivity and strong binding force for the adsorption of lithium ions. Therefore, although AlLi-LDH performs well in the adsorption of lithium ions, in practical applications, how to effectively desorb these ions from AlLi-LDH, especially while maintaining the structural integrity of the material, is a problem that needs further research and solution. In summary, the difficulty of desorption of lithium adsorbed by the Al-O octahedral ring in AlLi-LDH is mainly determined by its special structure and chemical properties, including the transformation of space groups, the rigidity of the Al-O octahedral ring, and the strong interaction between the aluminum-lithium layered double hydroxide and lithium ions. These factors work together to make it difficult to desorb the aluminum-lithium layered double hydroxide by simple physical methods after adsorbing lithium ions.
[0009] In addition, the prior art also directly uses aluminum hydroxide to extract and adsorb lithium-containing solutions, but the reversible adsorption capacity of aluminum hydroxide for lithium hydroxide is small and the elution is difficult; at the same time, the adsorption capacity of aluminum hydroxide for lithium chloride, lithium sulfate and lithium carbonate in the solution is small, which further limits the industrial application of aluminum hydroxide adsorbent. Moreover, when lithium hydroxide is adsorbed and converted into aluminum-lithium LDH, the current method of aluminum-lithium LDH cannot completely elute lithium ions.
[0010] Based on this, in the lithium ion extraction method of the present invention: on the one hand, in the adsorption link, aluminum hydroxide is activated and used as an adsorption subject to adsorb the lithium-containing solution, and aluminum-lithium LDH is generated by coprecipitation reaction to complete the adsorption of lithium ions in the lithium-containing solution. The generation process of aluminum-lithium LDH, which is widely used for lithium ion adsorption, is used as the adsorption process of lithium ions in the lithium-containing solution. Compared with the use of aluminum-lithium LDH to adsorb the lithium-containing solution, the adsorption amount of lithium ions by the aluminum hydroxide adsorbent is greatly improved.
[0011] On the other hand, in the desorption link, the aluminum lithium LDH is subjected to low-temperature calcination in the range of 200 to 600°C, and then assisted by the desorption effect of the desorbent, so that the lithium ions can be fully eluted effectively. Specifically, calcination at the above temperature can remove some impurity ions, and the structure of the aluminum lithium LDH after calcination can be restored to achieve a reversible cycle of lithium ion adsorption and desorption, so that the lithium ions in the aluminum lithium LDH can be efficiently desorbed; at the same time, the aluminum lithium LDH is only an intermediate product in the process of extracting lithium ions, so the desorption environment of the aluminum lithium LDH is less restricted. The desorbent of the present invention is selected as magnesium chloride, ferric chloride, magnesium sulfate or ferric sulfate solution, and the desorbent is weakly acidic, and the desorption rate is higher than that of a neutral or alkaline desorption environment. In addition, the desorption slag generated after desorption is alkali-dissolved to form an aluminum salt solution and an alkali-dissolved slag, wherein the aluminum salt solution is used to prepare the raw material of active aluminum hydroxide, and the prepared active aluminum hydroxide is used for the next lithium ion adsorption process to achieve the regeneration of the adsorbent.
[0012] Furthermore, the concentration of lithium ions in the lithium-containing solution is 50-500 mg / L, the adsorption temperature is 80-90° C., and the adsorption time is 1-2 hours. This extraction method is particularly suitable for lithium-containing solutions with lower concentrations, thereby achieving efficient utilization of lithium resources.
[0013] Furthermore, the alkaline lithium-containing solution is specifically prepared by pre-adjusting the lithium ion concentration of the lithium-containing solution with ammonia water or sodium hydroxide to be the same as the hydroxide ion concentration.
[0014] Furthermore, the generated aluminum lithium LDH is subjected to low temperature calcination, wherein the calcination temperature is 200 to 500° C. and the calcination time is 30 to 90 minutes.
[0015] Furthermore, the lithium ion concentration in the obtained lithium-rich solution is not less than 5 g / L.
[0016] Furthermore, the concentration of metal cations contained in the desorbent in the lithium-rich solution is lower than 10 mg / L.
[0017] Furthermore, the desorption residue is dissolved in alkali to form an aluminum salt solution and an alkali-soluble slag, wherein the aluminum salt solution is used to prepare active aluminum hydroxide and is recycled, specifically comprising: the desorption residue is dissolved in a sodium hydroxide solution, and a sodium aluminate solution and an alkali-soluble slag are obtained after solid-liquid separation, and an acid solution is added dropwise to the sodium aluminate solution, and the pH value at the end point of the addition is controlled to be between 10 and 14, and active aluminum hydroxide is obtained after separation and drying.
[0018] Furthermore, the adsorption capacity of activated aluminum hydroxide for lithium ions is 38-42 mg·g -1 , the desorption rate of the lithium ions reaches 80% to 95%.
[0019] Further, the alkaline slag is acid-dissolved to obtain a desorbent again, wherein the concentration of the acid solution used is 0.04-0.1 mol / L; the pH of the desorbent is adjusted between 5 and 7, and the concentration of the metal cations contained therein is 0.01-0.04 mol / L. The obtained desorbent is used in the next aluminum-lithium LDH desorption process for recycling.
[0020] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0021] (1) The present invention realizes efficient adsorption of lithium ions by utilizing the process of generating aluminum lithium LDH, and the adsorption capacity of activated aluminum hydroxide for lithium ions is 38 to 42 mg·g -1 , which is higher than the adsorption capacity of the existing aluminum-lithium LDH adsorbent; and by converting lithium ions into the form of aluminum-lithium LDH, highly selective separation of lithium ions is achieved, and the extraction rate of impurity ions is basically zero. At the same time, this extraction method is particularly suitable for low-concentration lithium-containing solutions, specifically lithium-containing solutions with a concentration between 50 and 500 mg / L. After adsorption, the lithium ion concentration can be reduced to below 0.5 ppm, and the adsorption rate is relatively high, thereby realizing efficient utilization of lithium resources. In addition, through the optimized design of roasting and desorbent, efficient desorption of adsorbed lithium ions in the intermediate product aluminum-lithium LDH is achieved, thereby realizing the desorption of lithium ions and completing the whole process of lithium ion extraction.
[0022] (2) The present invention further optimizes the design of the lithium ion extraction method, dissolving the desorption residue obtained after desorption in a sodium hydroxide solution, obtaining a sodium aluminate solution and an alkaline slag after solid-liquid separation, and dripping the acid solution into the aluminum salt solution to control the pH value at the end point of the dripping to prepare the active aluminum hydroxide required for the next adsorption process. In addition, the alkaline slag is acid-dissolved and a new desorbent is prepared, thereby reducing the raw material consumption in the lithium ion extraction process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The figure is an overall flow chart of the lithium ion extraction method of the present invention.
[0024] Figure 2 This is the XRD diagram of the active aluminum hydroxide in Example 1 of the present invention.
[0025] Figure 3 This is the XRD diagram of the aluminum-lithium LDH before calcination in Example 1 of the present invention.
[0026] Figure 4 1 is the XRD diagram of the aluminum-lithium LDH after calcination in Example 1, Example 5 and Example 6 of the present invention.
[0027] Figure 5 This is the XRD diagram of the aluminum-lithium LDH after adsorption, calcination at 300° C., and desorption of lithium in Example 2 of the present invention.
[0028] Figure 6 This is a microscopic morphology of the active aluminum hydroxide in Example 1 of the present invention.
[0029] Figure 7 This is a microscopic morphology of the aluminum-lithium LDH before calcination in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings and embodiments.
[0031] In the following embodiments, "lithium hydroxide solution" is used as the lithium-containing solution only to illustrate the technical effect of the present invention, and it should not be understood that the lithium-containing solution is limited to the above range. The cations in the lithium-containing solution include but are not limited to Li + 、Na + , K + Mg 2+ , Ca 2+ 、Co 2+ 、Ni 2+ ; Anions include but are not limited to Cl - 、SO 4 2- , CO 3 2- , HCO 3- 、NO 3 - OH - For other lithium-containing solutions, ammonia water or sodium hydroxide is used to adjust the concentration of hydroxide in the lithium-containing solution; the concentration of hydroxide in the mixed solution can also be adjusted after adding active aluminum hydroxide; or active aluminum hydroxide is added to the alkaline solution and then mixed with the lithium-containing solution.
[0032] Example 1
[0033] The lithium ion extraction method of this embodiment specifically includes the following steps:
[0034] (1) Alumina (η AO ) method to determine the aluminum concentration in the existing sodium aluminate solution, and prepare a new sodium aluminate solution to adjust the concentration of the existing sodium aluminate solution to 150.00 g·L -1 ; The concentration is 1.8 mol·L -1 The hydrochloric acid is slowly added dropwise to the sodium aluminate solution, and the pH value at the end of the addition is 13. The obtained material after solid-liquid separation is dried in an oven at 80°C to obtain active aluminum hydroxide;
[0035] (2) Using lithium hydroxide as the lithium source, the lithium ion concentration is 500 ppm, and then adding active aluminum hydroxide to the lithium-containing solution for adsorption, controlling the adsorption temperature to 90°C, and naturally cooling to 30°C after adsorption for 1 hour;
[0036] (3) calcining the prepared aluminum lithium LDH in an air atmosphere at a temperature of 400° C. for 1 h;
[0037] (4) Using magnesium chloride as a desorbent, the desorption time is 5 hours, and the desorption is repeated for multiple cycles until the lithium ion concentration in the lithium-rich solution reaches 5 g / L and the magnesium ion concentration is less than 10 ppm;
[0038] (5) dissolving the desorption residue obtained after desorption in a sodium hydroxide solution, and obtaining a sodium aluminate solution and an alkaline soluble residue after solid-liquid separation, and the obtained sodium aluminate solution is used for preparing active aluminum hydroxide in step 1);
[0039] (6) The obtained alkaline slag is dissolved in 0.1 mol / L dilute hydrochloric acid to prepare a desorbent magnesium chloride, and the concentration of magnesium ions therein is adjusted to 0.04 mol / L and the pH is 6-7, so as to be used as the desorbent required in step 4).
[0040] In this embodiment, the microscopic morphology of the active aluminum hydroxide in step 1) and the aluminum lithium LDH generated in step 2) were observed, and the results were as follows: Figure 6 , Figure 7 As shown. Combined Figure 6 , Figure 7 It can be seen that aluminum-lithium LDH is generated by controlling the contact conditions between aluminum hydroxide and the lithium-containing solution.
[0041] The active aluminum hydroxide prepared in step 1) was subjected to XRD analysis, and the results were as follows: Figure 2 As shown, the aluminum lithium LDH generated in step 2) is subjected to XRD analysis, and the results are as follows Figure 3 As shown. Combined Figure 2 , Figure 3 It can be seen that aluminum-lithium LDH is generated by controlling the contact conditions between aluminum hydroxide and the lithium-containing solution.
[0042] The adsorption capacity of the aluminum-lithium LDH generated in step 2) was tested, and the adsorption capacity of lithium ions was measured to be 40 mg g -1 .
[0043] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this embodiment was 95%.
[0044] Comparative Example 1
[0045] The lithium ion extraction method of this embodiment is different from that of Embodiment 1 in that the calcination temperature in step 3) is 150° C.; the remaining operations and parameters are basically the same.
[0046] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this comparative example was 65%.
[0047] Comparative Example 2
[0048] The lithium ion extraction method of this embodiment is different from that of Embodiment 1 in that the calcination temperature in step 3) is 650° C.; the remaining operations and parameters are basically the same.
[0049] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this comparative example was 10%.
[0050] Comparative Example 3
[0051] The lithium ion extraction method of this comparative example is different from that of Example 1 in that hot water is used for desorption in step 4), the pH of the solution during the desorption process is 7, and step 6 is deleted; the remaining operations and parameters are basically the same.
[0052] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this comparative example was 60%.
[0053] Comparative Example 4
[0054] The lithium ion extraction method of this comparative example is different from that of Example 1 in that: in step 2), lithium chloride is used as a lithium source, and the hydroxide concentration of the lithium chloride solution is not adjusted; the operating steps and parameters are basically the same.
[0055] The adsorption capacity of active aluminum hydroxide in step 2) was tested, and the adsorption capacity of lithium ions was measured to be 2 mg g -1 .
[0056] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured. The lithium ions were basically adsorbed on the powder surface, and aluminum-lithium LDH was not formed. It was easier to desorb. The desorption rate of this comparative example was 95%.
[0057] Example 2
[0058] The lithium ion extraction method of this embodiment specifically includes the following steps:
[0059] (1) Alumina (η AO ) method to determine the aluminum concentration in the existing sodium aluminate solution, and prepare a new sodium aluminate solution to adjust the concentration of the existing sodium aluminate solution to 100 g·L -1 ; The concentration is 2 mol·L -1 The hydrochloric acid is slowly added dropwise to the sodium aluminate solution, and the pH value at the end of the addition is 14. The obtained material after solid-liquid separation is dried in an oven at 80°C to obtain active aluminum hydroxide;
[0060] (2) Using lithium hydroxide as the lithium source, the lithium ion concentration is 100 ppm, and then adding active aluminum hydroxide to the lithium-containing solution for adsorption, controlling the adsorption temperature to 90°C, and naturally cooling to 30°C after adsorption for 2 hours;
[0061] (3) calcining the prepared aluminum lithium LDH in an air atmosphere at a temperature of 300° C. for 1.5 h;
[0062] (4) magnesium sulfate is used as a desorbent, the desorption time is 5 hours, and the desorption is repeated for multiple cycles until the lithium ion concentration in the lithium-rich solution reaches 6 g / L and the magnesium ion concentration is less than 10 ppm;
[0063] (5) dissolving the desorption residue obtained after desorption in a sodium hydroxide solution, and obtaining a sodium aluminate solution and an alkaline soluble residue after solid-liquid separation, and the obtained sodium aluminate solution is used for preparing active aluminum hydroxide in step 1);
[0064] (6) The obtained alkaline slag is dissolved in 0.04 mol / L dilute sulfuric acid to prepare a desorbent magnesium sulfate, wherein the concentration of magnesium ions is adjusted to 0.02 mol / L and the pH is adjusted to 6-7, so as to be used as the desorbent required in step 4).
[0065] XRD analysis was performed on the aluminum-lithium LDH generated in step 2), the aluminum-lithium LDH calcined in step 3), and the aluminum-lithium LDH desorbed in step 4. The results are as follows: Figure 5 As shown. Combined Figure 5 It can be seen that the characteristic peaks of aluminum hydroxide at around 18.76°, 20.56° and 40.78° are all Figure 5 It is shown in the spectrum after lithium desorption, and the peak width of the characteristic peak is relatively wide. This shows that after desorption of lithium ions, the structure of the adsorbent is basically restored and can be repeatedly used for the adsorption of lithium ions.
[0066] The adsorption capacity of the aluminum-lithium LDH generated in step 2) was tested, and the adsorption capacity of lithium ions was measured to be 42 mg g -1 .
[0067] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this embodiment was 92%.
[0068] Example 3
[0069] The lithium ion extraction method of this embodiment specifically includes the following steps:
[0070] (1) Alumina (η AO ) method to determine the aluminum concentration in the existing sodium aluminate solution, and prepare a new sodium aluminate solution to adjust the concentration of the existing sodium aluminate solution to 80 g·L -1 ; The concentration is 1 mol·L -1 The hydrochloric acid is slowly added dropwise to the sodium aluminate solution, and the pH value at the end of the addition is 10. The obtained material after solid-liquid separation is dried in an oven at 80°C to obtain active aluminum hydroxide;
[0071] (2) Using lithium hydroxide as the lithium source, the lithium ion concentration is 50 ppm, and then adding active aluminum hydroxide to the lithium-containing solution for adsorption, controlling the adsorption temperature to 80°C, and naturally cooling to 30°C after adsorption for 2 hours;
[0072] (3) calcining the prepared aluminum lithium LDH in an air atmosphere at a temperature of 500° C. for 30 min;
[0073] (4) using ferric chloride as a desorbent, the desorption time is 5 hours, and the desorbent is circulated until the lithium ion concentration in the lithium-rich solution reaches 5 g / L and the iron ion concentration is less than 10 ppm;
[0074] (5) dissolving the desorption residue obtained after desorption in a sodium hydroxide solution, and obtaining a sodium aluminate solution and an alkaline soluble residue after solid-liquid separation, and the obtained sodium aluminate solution is used for preparing active aluminum hydroxide in step 1);
[0075] (6) The obtained alkaline slag is dissolved in 0.1 mol / L dilute hydrochloric acid to prepare a desorbent ferric chloride, and the concentration of iron ions therein is adjusted to 0.02 mol / L and the pH is 6-7, so as to be used as the desorbent required in step 4).
[0076] The adsorption capacity of the aluminum-lithium LDH generated in step 2) was tested, and the adsorption capacity of lithium ions was measured to be 38 mg g -1 .
[0077] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this embodiment was 88%.
[0078] Example 4
[0079] The lithium ion extraction method of this embodiment specifically includes the following steps:
[0080] (1) Alumina (η AO ) method to determine the aluminum concentration in the existing sodium aluminate solution, and prepare a new sodium aluminate solution to adjust the concentration of the existing sodium aluminate solution to 80 g·L -1 ; The concentration is 1 mol·L -1 The hydrochloric acid is slowly added dropwise to the sodium aluminate solution, and the pH value at the end of the addition is 10. The obtained material after solid-liquid separation is dried in an oven at 80°C to obtain active aluminum hydroxide;
[0081] (2) Using lithium hydroxide as the lithium source, the lithium ion concentration is 300 ppm, and then adding active aluminum hydroxide to the lithium-containing solution for adsorption, controlling the adsorption temperature to 85°C, and naturally cooling to 30°C after adsorption for 1.5 hours;
[0082] (3) calcining the prepared aluminum lithium LDH in an air atmosphere at a temperature of 500° C. for 30 min;
[0083] (4) using ferric sulfate as a desorbent, the desorption time is 5 h, and the desorbent is circulated until the lithium ion concentration in the lithium-rich solution reaches 5 g / L and the iron ion concentration is less than 10 ppm;
[0084] (5) dissolving the desorption residue obtained after desorption in a sodium hydroxide solution, and obtaining a sodium aluminate solution and an alkaline soluble residue after solid-liquid separation, and the obtained sodium aluminate solution is used for preparing active aluminum hydroxide in step 1);
[0085] (6) The obtained alkaline slag is dissolved in 0.04 mol / L sulfuric acid to prepare a desorbent ferric sulfate, wherein the concentration of iron ions is adjusted to 0.02 mol / L and the pH is adjusted to 5-6, so as to be used as the desorbent required in step 4).
[0086] The adsorption capacity of the aluminum-lithium LDH generated in step 2) was tested, and the adsorption capacity of lithium ions was measured to be 42 mg g -1 .
[0087] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this embodiment was 86%.
[0088] Example 5
[0089] The lithium ion extraction method of this embodiment is different from that of Embodiment 1 in that the calcination temperature in step 3) is 200° C.; the remaining operations and parameters are basically the same.
[0090] The aluminum lithium LDH after calcination in step 3) was subjected to XRD analysis, and the results were as follows: Figure 4 shown.
[0091] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this embodiment was 90%.
[0092] Example 6
[0093] The lithium ion extraction method of this embodiment is different from that of Embodiment 1 in that the calcination temperature in step 3) is 600° C.; the remaining operations and parameters are basically the same.
[0094] The aluminum lithium LDH after calcination in step 3) was subjected to XRD analysis, and the results were as follows: Figure 4 shown.
[0095] The ratio of lithium ions desorbed to lithium ions adsorbed during the generation of aluminum-lithium LDH was measured, and the desorption rate of this embodiment was 80%.
[0096] In Example 1, Example 5 and Example 6, the calcination temperatures are different. The aluminum-lithium LDH after calcination is subjected to XRD analysis. The results are as follows: Figure 4 As shown. Combined Figure 4 It can be seen that when the calcination temperature of aluminum-lithium LDH increases to 600°C, a trace amount of aluminum oxide will be generated, which will reduce the recycling adsorption capacity of the material. Therefore, the calcination temperature should be lower than 600°C.
Claims
1. A method for extracting lithium ions, characterized in that: include: Contacting or mixing the active aluminum hydroxide with the alkaline lithium-containing solution to generate aluminum-lithium LDH to achieve adsorption of lithium ions in the lithium-containing solution; The generated aluminum-lithium LDH is subjected to low-temperature calcination at a temperature of 200 to 600° C.; Desorbing the calcined product by using a desorbent, obtaining a lithium-rich solution and a desorbed slag material after solid-liquid separation, wherein the desorbent is magnesium chloride, ferric chloride, magnesium sulfate or ferric sulfate solution; The desorption residue is dissolved in alkali to form an aluminum salt solution and an alkali-dissolved residue, wherein the aluminum salt solution is used to prepare active aluminum hydroxide and is recycled.
2. The method for extracting lithium ions according to claim 1, characterized in that: The concentration of lithium ions in the lithium-containing solution is 50-500 mg / L, the adsorption temperature is 80-90° C., and the adsorption time is 1-2 hours.
3. The method for extracting lithium ions according to claim 2, characterized in that: The alkaline lithium-containing solution is specifically prepared by pre-adjusting the lithium-ion concentration of the lithium-containing solution to be equal to the hydroxide ion concentration using ammonia water or sodium hydroxide.
4. The method for extracting lithium ions according to claim 1, characterized in that: The generated aluminum lithium LDH is subjected to low temperature calcination, wherein the calcination temperature is 300-500° C. and the calcination time is 30-90 minutes.
5. The method for extracting lithium ions according to any one of claims 1 to 4, characterized in that: The lithium ion concentration in the obtained lithium-rich solution is not less than 5g / L.
6. The method for extracting lithium ions according to claim 5, characterized in that: The concentration of the metal cations contained in the desorbent in the lithium-rich solution is lower than 10 mg / L.
7. The method for extracting lithium ions according to claim 6, characterized in that: The desorption residue is dissolved in alkali to form an aluminum salt solution and an alkali-soluble residue, wherein the aluminum salt solution is used to prepare active aluminum hydroxide and is recycled. The method specifically comprises: dissolving the desorption residue in a sodium hydroxide solution, obtaining a sodium aluminate solution and an alkali-soluble residue after solid-liquid separation, dripping an acid solution into the sodium aluminate solution, controlling the pH at the end point of dripping to be between 10 and 14, and obtaining active aluminum hydroxide after separation and drying.
8. The method for extracting lithium ions according to claim 7, characterized in that: The adsorption capacity of the active aluminum hydroxide for lithium ions is 38 to 42 mg·g -1 , the desorption rate of the lithium ions reaches 80% to 95%.
9. The method for extracting lithium ions according to any one of claims 1 to 4, characterized in that: The alkaline slag is acid-dissolved to obtain a desorbent again, wherein the concentration of the acid solution used is 0.04-0.1 mol / L; the pH of the desorbent is adjusted between 5 and 7, and the concentration of the metal cations contained in the desorbent is 0.02-0.04 mol / L, and the desorbent is recycled.
Citation Information
Patent Citations
Preparation method of lithium hydroxide
CN110002475B
Lithium ion adsorbent, preparation method thereof and lithium ion extraction method
CN117299069A